Function, Applicability, and Properties of a Novel Flexible Total Ossicular Replacement Prosthesis With a Silicone Coated Ball and Socket Joint. Issue 6 (July 2018) - Stoppe, Thomas; Bornitz, Matthias; Lasurashvili, Nikoloz; Sauer, Kirsten; Zahnert, Thomas; Zaoui, Karim; Beleites, Thomas
Abstract : Hypothesis: A total ossicular replacement prosthesis (TORP) with a silicone coated ball and socket joint (BSJ) is able to compensate pressure changes and therefore provide better sound transmission compared with rigid prostheses. Background: Dislocation and extrusion are known complications after TORP reconstruction, leading to revisions and recurrent hearing loss. Poor aeration of the middle ear, scar tension, and static pressure variations in conjunction with rigid prosthesis design causes high tension at the implant coupling points. Methods: A novel TORP prototype with a silicone coated BSJ has been developed. Experimental measurements were performed on nine fresh cadaveric human temporal bones of which five were used for a comparison between rigid TORP and flexible TORP tympanoplasty. The middle ear transfer function was measured at ambient pressure and at 2.5 kPa, both positive and negative pressure, applied in the ear canal. Results: The flexible TORP design yields a better transmission of sound after implantation and at negative pressure inside the tympanic cavity, compared with rigid TORP. In average, it provides an equivalent sound transfer like the intact middle ear. At positive pressure, the flexible TORP performs slightly worse. Both performed worse than the intact middle ear, which is related to an uplifting of the prostheses. Conclusion: The findings may be considered preliminary as this experimental study was limited to just one of the many different possible situations of tympanoplasty and it involved a small sample size. Nevertheless, the results with the flexible TORP were promising and could encourage further investigations on such prostheses.